Role Play-Based Emergency Drill: A Contextual Learning Model to Improve Early Childhood Preparedness in Facing Natural Disasters - Faizin, Imam; Suharini, Erni; Diana, Diana (Universitas Negeri Semarang, 2025)
This study aims to examine the effectiveness of the role-play-based emergency drill model as a contextual learning approach in improving early childhood disaster preparedness. The study was conducted at RA Tamrinusyibyan, an early childhood education unit located in an earthquake-prone area. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results of the study indicated that disaster simulation activities carried out through role-playing were able to improve children's understanding of danger signs and evacuation procedures and form responsive and empathetic behavior in emergency situations. Children showed high enthusiasm, were able to follow instructions well, and began to apply the concept of preparedness in everyday life. Teachers play an important role as facilitators who package activities in a fun and educational play atmosphere. These findings indicate that this model supports thematic and holistic learning and forms strong characters in children from an early age. The role-play-based emergency drill model is recommended for implementation in early childhood education units, especially in disaster-prone areas, as an effort to provide effective and child-friendly risk mitigation education.